Islamic Values-Based Madrasah Branding Strategy: A Case Study of MTsN 6 Sleman and the Development of the KIPOO Conceptual Model - Afandi, Ali; Sutrisno, Sutrisno; Munastiwi, Erni (Jurnal Pendidikan Islam, 2025)
Purpose – This study aims to explain why MTsN 6 Sleman, Yogyakarta, Indonesia, was designated as a Rintisan Madrasah Unggul (RMU), analyze the branding and institutional promotion strategies following that designation, and formulate a conceptual model of Islamic values-based madrasah branding. Design/methods/approach – This study uses a qualitative approach with an instrumental case study design. Data were collected through in-depth interviews, limited participant observation, and documentation analysis of 15 informants consisting of leaders, teachers, staff, students, and parents. The data were analyzed thematically based on the symbolic interactionism framework. Findings – The findings show that the designation of MTsN 6 Sleman as an RMU was supported by institutional readiness that included adaptive capacity toward policy, disciplined academic governance, the quality of resources and facilities, and a strong religious and professional culture. Following the RMU designation, branding was developed through strengthening institutional identity, consolidating internal and external mindsets, differentiating flagship programs such as tahfidz, research, and robotics, and value-based multichannel promotion through direct communication and digital media. Based on these findings, this study formulates the KIPOO Kite Model, which places branding and promotion as an integrative mechanism that connects context, input, process, output, and outcome. Research implications – These findings provide a reference for madrasahs in building values-based branding through strengthening vision, differentiating flagship programs, institutionalizing an internal development team, and carrying out digital and face-to-face promotion consistent with institutional identity.